2022
DOI: 10.1101/2022.12.07.519536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the impacts of an invasive weed on habitat quality and prey availability for tiger snakes (Notechis scutatus) in urban wetlands

Abstract: Invasive plants are a threat to natural ecosystems worldwide with urban wetlands being some of the most susceptible and highly modified environments of all. The tiger snake (Notechis scutatus) is a top predator that persists in urban wetlands in south-western Australia, many of which have been degraded by introduced kikuyu grass (Cenchrus clandestinus). To evaluate the potential impact of kikuyu grass on habitat quality for western tiger snakes we quantified the structural features of habitats within wetlands … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…For tiger snakes, sites dominated by kikuyu and native vegetation did not differ substantially with respect to prey availability, temperature or predation pressure for tiger snakes (Cornelis et al 2022), so we suspect these factors are not directly driving the observed differences in tiger snake movements.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…For tiger snakes, sites dominated by kikuyu and native vegetation did not differ substantially with respect to prey availability, temperature or predation pressure for tiger snakes (Cornelis et al 2022), so we suspect these factors are not directly driving the observed differences in tiger snake movements.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings add to an increased understanding of how changes in habitat composition, driven by invasive vegetation, can affect space use by animals. Our current findings suggest that management plans for urban wetlands in the Perth urban area should improve structural complexity of homogenous kikuyu habitat by planting native species to support the predators in these ecosystems (Cornelis et al 2022). However, it remains to be determined if and how this grass affects reproductive success and long-term survival of tiger snakes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations